2015
DOI: 10.1051/parasite/2015001
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and prevalence of gastrointestinal parasites in seven non-human primates of the Taï National Park, Côte d’Ivoire

Abstract: Parasites and infectious diseases are well-known threats to primate populations. The main objective of this study was to provide baseline data on fecal parasites in the cercopithecid monkeys inhabiting Côte d’Ivoire’s Taï National Park. Seven of eight cercopithecid species present in the park were sampled: Cercopithecus diana, Cercopithecus campbelli, Cercopithecus petaurista, Procolobus badius, Procolobus verus, Colobus polykomos, and Cercocebus atys. We collected 3142 monkey stool samples between November 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 63 publications
(60 reference statements)
12
88
2
2
Order By: Relevance
“…Neste sentido, o diagnóstico de parasitos com potencial zoonótico tais como T. trichiura, Strongyloides sp., T. canis e Ancylostoma sp., merece destaque não somente porque são um risco para a saúde dos animais, mas também porque podem afetar severamente a saúde das pessoas que trabalham diretamente com estes animais, tais como veterinários, biólogos, zootecnistas, tratadores, entre outros (Freitas et al 2001, Sibaja-Morales et al 2009, Public Health Agency of Canada, 2011. Strongyloides fuelleborni e S. stercoralis também apresentam potencial zoonótico, já que são descritos em humanos e primatas não humanos (Mbaya & Udendeye 2011, Viney & Lok 2011, Mafuyai et al 2013, Kouassi et al 2015. Infestações por carrapatos dos gêneros Amblyomma e Ornithodoros (Barros-Battesti et al 2006, Dantas-Torres et al 2010) são frequentes em humanos, provocando reações que variam desde prurido e lesões na pele até distúrbios sistêmicos (Reck et al 2014).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Neste sentido, o diagnóstico de parasitos com potencial zoonótico tais como T. trichiura, Strongyloides sp., T. canis e Ancylostoma sp., merece destaque não somente porque são um risco para a saúde dos animais, mas também porque podem afetar severamente a saúde das pessoas que trabalham diretamente com estes animais, tais como veterinários, biólogos, zootecnistas, tratadores, entre outros (Freitas et al 2001, Sibaja-Morales et al 2009, Public Health Agency of Canada, 2011. Strongyloides fuelleborni e S. stercoralis também apresentam potencial zoonótico, já que são descritos em humanos e primatas não humanos (Mbaya & Udendeye 2011, Viney & Lok 2011, Mafuyai et al 2013, Kouassi et al 2015. Infestações por carrapatos dos gêneros Amblyomma e Ornithodoros (Barros-Battesti et al 2006, Dantas-Torres et al 2010) são frequentes em humanos, provocando reações que variam desde prurido e lesões na pele até distúrbios sistêmicos (Reck et al 2014).…”
Section: Discussionunclassified
“…Para o diagnóstico de parasitos gastrointestinais (PGI), as amostras foram processadas pelos métodos: microscopia direta, flutuação de Sheather modificado (com solução hipersaturada de açúcar) (Sibaja-Morales et al 2009) e de sedimentação espontânea (Freitas et al 2001(Freitas et al , 2002a. A identificação dos oocistos e ovos de PGI seguiu a descrição morfológica de Zajac & Conboy (2006), Urquhart et al (2008) e Kouassi et al (2015).…”
Section: Methodsunclassified
“…A study was conducted on the effect of bLf with different iron-saturation levels as well as an Lf hydrolysate (bLfh) on parasite viability [45]. The IC 50 (concentration that inhibits 50% of parasites in blood) value was 2.7 mg/ml apobLf for B. caballi, but no effect was observed against B. equi; this result was similar even when the culture medium was treated with a heparin column to remove the bLf. The inhibitory effect of bLf may have been caused by the inactivation of a growth factor in the culture medium.…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…However, E. histolytica has been reported in non-human primates (NHP) such as Cercopithecus aethiops (vervet), C. albogularis (Sykes' monkey) and Papio anubis (olive baboon) [47][48][49][50]. Although the prevalence of E. histolytica is low in NHP, it represents a risk of zoonosis for zoo workers who coexist with NHP.…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…According to STRIER (1995) and KOUASSI et al (2015), Ancylostoma and Strongyloide are the most commonly found helminths in primates; and PISSINATTI (2001) states that, in new world primates, parasitic diseases are the most prevalent findings at necropsies.…”
Section: Introductionmentioning
confidence: 99%